Auriculoterapia e a síndrome de Burnout em enfermeiras da atenção primária à saúde - Silva, Cleyton Cézar Souto (2018)
Auriculotherapy uses specific ear points to treat various body disorders. Burnout Syndrome is a response to chronic stress and has three dimensions: emotional exhaustion, dehumanization and disappointment with work. The aim of the study is to analyze the application of auriculotherapy in coping with and controlling the Burnout Syndrome in Primary Health Care nurses. This is a descriptive study, with a quantitative approach and quasi-experimental design, of pre-test and post-test types. It was carried out in the Primary Health Care units of the municipality of Natal, RN. The non-probabilistic sample consisted of 75 nurses diagnosed with the disease at mild, moderate and severe levels by the Burnout Characterization Scale. Salivary cortisol was collected in all nurses to compare the concentration before and after auriculotherapy in the workers identified with the syndrome, and the hormone dosage was performed using the competitive ELISA technique. Twelve sessions were performed and the points used were: specific action (anxiety), Traditional Chinese Medicine (liver, spleen/pancreas and heart), nervous system (Shem Men and sympathetic) and endocrine system (adrenal). A favorable technical advice was obtained from the Research Ethics Committee (CEP/UFRN), protocol no. 2.444.525, and registered on the platform of the Brazilian Registry of Clinical Trials under the number RBR-4xbqbw. Data were collected from January to June of 2017 through a sociodemographic and occupational questionnaire, BCS and salivary cortisol by the Salivette™ device. Descriptive statistics techniques were used with frequency measures for categorical variables. In the inferential analysis, the ChiSquare test was used to verify the association between categorical variables: marital status, children and professional qualification. Subsequently, the normality of the data for the numerical variables was tested using the Kolmogorov Smirnov test, the Student's t test, the Mann-Whitney test and analysis of variance were used to compare the groups. All dimensions of Burnout Characterization Scale presented alpha values above 0.70: exhaustion = 0.943; dehumanization = 0.824; disappointment at work 0.738. Primary Health Care nurses had a moderate percentage of emotional exhaustion (74.7%), accompanied by mild dehumanization (81.3%) and slight disappointment at work (60%). The prevalence of Burnout Syndrome at levels was: severe (n = 2), moderate (n = 5) and mild (n = 64). Only four nurses did not present the disease. Correlations between socio-demographic and occupational variables showed weak statistical significance for the negative correlations between exhaustion and length of service; and between disappointment and length of service; and weak positive correlations between dehumanization with exhaustion and deception; and between deception and exhaustion, as well as a strong statistical tendency for the positive correlation between disappointment and age. Analysis of variance between Burnout Characterization Scale dimensions revealed a statistically significant difference between all dimensions of the disease. Comparison of salivary cortisol within the groups (mild, moderate, severe, and nonsickness Burnout) between collection shifts (morning and afternoon) showed statistical significance among the groups of mild, severe and non-disease Burnout Syndrome. There was no significant association between salivary cortisol concentrations and the variables time of service and workload. Comparing the concentration of salivary cortisol (morning and evening) before and after the intervention, there was a significant reduction in the nurses who performed the therapy and who had the disease at a severe level. In conclusion, Burnout Syndrome is associated with service time of less than 8 years and 40-hour workweek and auriculartherapy reversed physical and mental symptoms in reducing the salivary cortisol concentration in nurses with a serious and average disease level.